Physical Characteristics and Sensory Analysis of Sorghum Noodles (Sorghum bicolor (L.) Moench) using Just About Right Scale: Karakteristik Fisik dan Analisis Sensori Mie Sorgum (Sorghum bicolor (L.) Moench) Menggunakan Skala Just About Right - novita, silvy (Universitas Muhammadiyah Sidoarjo, 2023)
Sorghum is a cereal that grows a lot in Indonesia, however, its utilization is still lacking due to the tannin content in sorghum which causes a bitter taste and a gritty texture. Fermentation is one of the solutions to improve the sensory quality of sorghum, the tannins in sorghum are degraded in the fermentation process into simpler compounds. Utilization of sorghum into sorghum noodles is expected to increase public interest in consuming sorghum as a local food ingredient. Process of sensory analysis of sorghum noodles using the Just about right (JAR) scale and penalty analysis method.Sensory analysis of sorghum noodles using the JAR scale and penalty analysis aims to develop and improve the characteristics of sorghum noodles. The method used in this research was a Randomized Block Design with two factors, namely the composition proportion of sorghum flour: palm flour and fermentation time, so that six combinations were obtained with three repetitions. The proportions of sorghum flour and palm flour include T1 (40:60), T2 (60:40), T3 (80:20) and fermentation time 0 hours (M1), fermentation time 48 hours (M2). Characterization of sorghum noodles was carried out to obtain sorghum noodles with the best treatment using the de garmo method.Sensory analysis using the JAR scale method and penalty analysis showed that taste, texture and appearance had an OAL of more than 20% with a P value ≤ 0.05, so that these three attributes need development to improve the characteristics of sorghum noodles. The development of sorghum noodles was carried out by fermenting sorghum flour with the sample code M2T2 which aims to degrade tannins. The results of the development showed that the OAL for fermented sorghum noodles was less than 20% and P value ≥ 0.05, which means that the opinion of the panelists on the characteristics of sorghum noodles was